Influence of ACE inhibitors on free radicals and reperfusion injury: pharmacological curiosity or therapeutic hope? - McMurray, J (1991)
1. The currently available evidence shows that thiol containing ACE inhibitors are free radical (FR) scavengers in vitro; in particular the OH. radical is effectively scavenged by these compounds. There is also good evidence that, in vivo, ACE inhibitors can preserve myocardial contractile function following a period of reversible ischaemia (by directly protecting myocytes and/or preserving coronary flow through protection of endothelial cells). These in vivo benefits are probably also due to FR scavening, mainly due to the presence of a thiol group but, also as a consequence of augmented prostanoid production. 2. Use of more relevant animal models and testing of a range of doses of ACE inhibitors might be undertaken before clinical investigation is considered. Because of its nature, however, the existence and importance of reperfusion injury in man will only be proven or disproven by pharmacological intervention. One option is to compare a thiol containing agent with absent or minimal haemodynamic effects with placebo as an adjunct to thrombolysis. This is the simplest approach. An alternative approach is to conduct a comparative study of a -SH containing ACE inhibitor and a non -SH containing ACE inhibitor given prior to thrombolysis. There are many problems with either approach. The lack of reliable measures of FR activity in man and difficulty in measuring accurately left ventricular function post-myocardial infarction means that mortality is likely to be the only reliable end-point in such a study.(ABSTRACT TRUNCATED AT 250 WORDS)